Development Model of Participatory-Based Demographic Control in Marginalized Communities - Ahmad Syaekhu; Sri Handayani; Irma Irma (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
Population density is positively correlated with fertility rates. Fertility is related to a woman's ability to reproduce. This study aims to: (1) What is the description of the participatory-based birth control counseling model for marginalized communities in Makassar City? (2) How to design a participatory-based birth control counseling model for marginalized communities in Makassar city? and (3) What is the validity, practicality, and effectiveness of the participatory-based birth control counseling model for marginalized communities in Makassar? This research is a type of Research & Development (R&D) research that is structured referring to the development of the model from Borg & Gall, and the modified Four - D. The syntax consists of problem analysis; preparation of lesson plans; development of learning tools; product testing and dissemination. The subjects of this research are marginal communities in three sub-districts. In this study, the extension model disseminated expert validation, three trials, and discussion group forums to determine the model's effectiveness in its implementation. The results obtained from the data analysis are: (1) The extension model to control the demographic figures is based on the active participation of marginalized communities. This counseling model is equipped with tools in the form of a module book, namely the birth rate control module, the prosperous family marriage module, and the long-term contraceptive method. (2) The design of the extension model is carried out through three stages, namely the pre-development stage, the development stage, and the trial stage. (3) The extension model controlling the demographic figures has been tested for validity, practicality, and effectiveness. The test results show that the extension model is valid, practical, and effective to use. The findings of this study are included in the MAD extension model, which includes model books and module books. The MAD extension model is intended for BKKBN extension workers/cades to support the increased active participation of marginalized communities in controlling birth rates.